Kultur Pesantren dalam Membentuk Sumber Daya Manusia yang Berkarakter 9 Budi Utama Santri - Mia Mia; Mamluatun Ni’mah; Salamah Eka Susanti (Cendekia, 2023)
Along with the times, culture in the world of education has an important role in human life and development. Where culture in education has an important role in human development and growth. So that education in Islamic boarding schools as a medium for printing human resources, researchers raised the title of Islamic boarding school culture in shaping human resources with the character of 9 Budi Utama Santri at Putri Hafshawaty Timur Zainul Hasan Genggong Islamic boarding school. 2) to find out the description of the santri in implementing the 9 Budi Utama Santri, 3) to find out the culture of the santri in the pesantren environment. Islamic boarding school culture is a habitual activity carried out by the students as an effort by the pesantren to build the character of the students. This type of research uses a qualitative approach. The data collection was obtained from information through direct observation techniques, in-depth interviews with Islamic boarding schools, and documentation. The results of this study in the management of human resources for students at Pondok Putri Hafshawaty Timur show: 1) the increase in the success of the number of students has increased very significantly from year to year. 2) an increase in the formation of the character of the students in obeying the rules at the Islamic boarding school. 3) improving the quality of boarding school administrators in fostering the character of students. So that education in Islamic boarding schools can be a good choice for the community as a source of seeking knowledge for their children.